A descriptive study of the reasons and consequences of pregnancy among single adolescent mothers in Lesotho - E.M. Yako; J.M. Yako (AOSIS, 2007)
The adolescents, who engage in unprotected sex, face the risk of unplanned pregnancy and sexually transmitted diseases. It is not clear why adolescents in Lesotho engage in unprotected sex and end up with unplanned pregnancies. In addition, it is not clear what the consequences of early childbearing are on the life of the adolescent and her infant. An understanding of the reasons why a number of adolescents engage in unprotected sex and the impact of pregnancy and early childbearing on the lives of adolescent mothers and their infants will potentially assist nurses and other health workers in adolescent health promotion programmes. The purpose of this study was: 1) to determine the adolescent mother's perceived reasons for pregnancy and 2) to determine pregnancy related joys, and problems faced by adolescent mother and her infant.